Peningkatan Pengetahuan Ibu Menyusui Tentang Hypnobreastfeeding dalam Upaya Meningkatkan Produksi ASI - Devina Anggrainy Dencik; Tri Restu Handayani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
One of the obstacles in the breastfeeding process is low milk production. This can be influenced by the mother's psychological condition. The happiness, comfort and calm of breastfeeding mothers has a positive impact on the breastfeeding process. This positive psychological condition can be obtained with hypnobreastfeeding, which is a relaxation technique to help smooth the breastfeeding process. Deep and regular relaxation makes the endocrine system, blood flow and other systems in the body function better, causing the endorphin hormones produced by the mother to flow to the breast. the baby through breast milk and also makes the baby feel comfortable and calm. This educational activity about hypnobreastfeeding was carried out at PMB Soraya Palembang 4 times, targeting post partum mothers and mothers who exclusively breastfeed their babies. The activity is planned to begin with education about hypnobreastfeeding and the factors that influence breast milk production and the factors that cause little breast milk. Next, distribute a pretest questionnaire containing the mother's attitude towards the ongoing breastfeeding process. Next is direct practice of hypnobreastfeeding and continued with evaluation using a posttest questionnaire with questions about the mother's attitude towards the breastfeeding process. Mothers' knowledge about hypnobreastfeeding on breast milk production has increased by 70%. It is hoped that all parties will improve their skills in realizing exclusive breastfeeding, one of which is through hypnobreastfeeding.